1991
DOI: 10.1172/jci115158
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of major histocompatibility complex alleles associated with the lupus anticoagulant.

Abstract: Autoantibodies to phospholipids (APA) occur frequently in systemic lupus erythematosus (SLE) and other autoimmune disorders and predispose to intravascular thromboses. Major histocompatibility complex (MHC) class II alleles (HLA-DR and DQ) were determined by restriction fragment length polymorphisms (RFLP) in 20 patients with APA (lupus anticoagulant). HLA-DQw7 (DQB1 *0301), linked to HLA-DR5 and -DR4 haplotypes, occurred in 70% and was significantly increased compared to 139 race-matched normal controls (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 34 publications
2
56
2
Order By: Relevance
“…Strong HLA class II antigen correlations have been found for several autoantibodies, including LA and ACA, in patients with some autoimmune diseases. 36 Therefore, further studies are necessary to clarify multiple genetic factors that are definitely linked with MMS in different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Strong HLA class II antigen correlations have been found for several autoantibodies, including LA and ACA, in patients with some autoimmune diseases. 36 Therefore, further studies are necessary to clarify multiple genetic factors that are definitely linked with MMS in different ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of T cell subsets (77), HLA class I1 associations (78), and IgG subclass distribution (79) and V gene analysis (80) suggest that T lymphocytes play an important role in autoantibody production and disease pathogenesis. It has recently been shown that T cells are critical in the transfer of A P S by bone marrow transplantation in an animal model (81).…”
Section: Immunopathogenesis Of Apsmentioning
confidence: 99%
“…Hartung et al [29] reported that HLA-DR4 and DR7 were increased in aCL positive patients in European SLE populations and aCL were significantly associated with DRw53. In a study of 20 patients with SLE and LA, an association with HLA-DQw7 (HLA DQB1*0301) linked to HLA-DR4 and/or -DR5 haplotypes was found in 70 % of patients and was significantly increased compared with 139 matched control individuals (p = 0.002) [30]. According to this study, several HLA-DQB1 alleles shared a common aminoacid sequence (positions 71-77) in the third hypervariable region of the outermost domain.…”
Section: Genes Associated With Antiphospholipid Syndromementioning
confidence: 99%